Morphologic Features of Carotid Plaque Rupture Assessed by Optical Coherence Tomography - Shindo, S. (AJNR Am J Neuroradiol, 2015)
BACKGROUND AND PURPOSE: Rupture of the plaque fibrous cap and subsequent thrombosis are the major causes of stroke. This study evaluated morphologic features of plaque rupture in the carotid artery by using optical coherence tomography in vivo. MATERIALS AND METHODS: Thirty-six carotid plaques with high-grade stenosis were prospectively imaged by optical coherence tomography. “Plaque rupture” was defined as a plaque containing a cavity that had overlying residual fibrous caps. The fibrous cap thickness was measured at its thinnest part for both ruptured and nonruptured plaques. The distance between the minimum fibrous cap thickness site and the bifurcation point was also measured. Optical coherence tomography identified 24 ruptured and 12 nonruptured plaques. RESULTS: Multiple ruptures were observed in 9 (38%) patients: Six patients had 2 ruptures in the same plaque, 2 patients had 3 ruptures in the same plaque, and 1 patient had 5 ruptures in the same plaque. Most (84%) of the fibrous cap disruptions were identified at the plaque shoulder and near the bifurcation point (within a 4.2-mm distance). The median thinnest cap thickness was 80 μm (interquartile range, 70–100 μm), and 95% of ruptured plaques had fibrous caps of <130 μm. Receiver operating characteristic analysis revealed that a fibrous cap thickness of <130 μm was the critical threshold value for plaque rupture in the carotid artery. CONCLUSIONS: Plaque rupture was common in high-grade stenosis and was located at the shoulder of the carotid plaque close to the bifurcation. A cap thickness of <130 μm was the threshold for plaque rupture in the carotid artery.